Influencer Marketing Effect on the Consumer’s Decision Making Process - Josifova, Andrea (2022)
The aim of the thesis is to assess the impact of influencer marketing on consumer’s decision making process in the Czech Republic. Qualitative approach for the research was applied and in-depth interviews with consistent consumers of the Czech market belonging to Generation Z were conducted in order to explore the behavioral tendencies of the consumer with reference to influencer marketing. Results indicate that consumers are most responsive to influencer’s transparency, expertise, and degree of activity. The perception of the brand was established as a significant intermediary between the influencer’s endorsed product and the consumer’s purchase decision. Additionally, a crucial element to deciding the consumer’s feelings towards the brand was the quality of the product. Brand control was found to have the greatest influence over the consumer’s purchase decision. Generally, the results indicate that the perception and feelings towards the brand which furthermore determine the degree of trust, respect and love for it, take prevalence compared to the influencer’s attributes over the consumer’s purchase decision. Nevertheless, the influencer’s characteristics remain of elevated significance as they dictate the tendency to follow the influencer, engage with them and command the degree of product visibility. Findings of the current study entail that influencer marketing is a powerful tool that impacts the consumer’s following and purchase decision. It is subject of further development and consequently adequate recommendations on transparentizing the influencer structure, generating more efficient and positive impact on the consumer’s purchase decision are provided based on the findings.